The Sukuk Effect on Stock Return Volatility in Indonesia - Legina Legina; Harjum Muharam; Ahmad Maulin Naufa (Perspektif Akuntansi, 2020)
The purpose of this research is to examine the effect of the announcement of Sukuk issuance to stock return volatility and to examine the phenomenon of time the varying volatility that occurs in the movement of stock returns and volatility. The data used in this research are daily closing price and trading volume incorporate Sukuk issued during the year 2009-2013 in the D-100 D+100 of Observation period. Samples utilized the purposive sampling technique to obtain the Samples of 13 companies. This study uses EGARCH (Exponential Generalized Autoregressive Conditional Heteroscedasticity) method of analysis. The results show that the best model for each sample in the EGARCH model is different. The results show that the phenomenon of time-varying volatility occurred in 13 samples. From 13 samples, event announcement of the Sukuk issuance does not affect the volatility of stocks returns except for Multi Adira Finance company. Furthermore, the trading volume affects the stock returns volatility on 9 companies, hence do not affect the other four companies.